PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA MASA PANDEMI COVID-19 DI SDN NO 123 BANTI DESA BANTI KEC. BARAKA KAB. ENREKANG - Siti Fatimah Ridwan; Vera Lonika Paliling; Nahdiah Nasir; Rahmawati Rahmawati; Diah Irawaty. A; Nurhikmah M; Muhammad Syukur Abdillah; Julaidi Julaidi; Irfan Abdillah; Yonas Febrianto K (STAI Darul Qalam Tangerang, 2021)
As of September 10, 2021, face-to-face learning will begin to be applied simultaneously to schools in Baraka District, Enrekang Regency, one of which is SDN No 123 Banti. Face-to-face learning during the COVID-19 pandemic certainly has its own challenges for teaching staff at SDN No 123 Banti, especially to make SDN No 123 Banti students comply with health protocols. Group 50 Real Work Lecture (KKN) students, University of Muhammadiyah Parepare who were stationed in Banti Village, took the initiative to conduct counseling on Clean and Healthy Life Behavior (PHBS) to students of SD Negeri 123 Banti, as well as explaining the process of spreading the virus which is expected to provide students with the opportunity to SDN No 123 Banti students understand the importance of implementing health protocols during face-to-face learning during the COVID-19 pandemic